JURNAL NASIONAL TEKNIK ELEKTRO DAN TEKNOLOGI INFORMASI: istem Penghindar Tabrakan Frontal Berbasis Logika Fuzzy - Noor Cholis Basjaruddin, Kuspriyanto Kuspriyanto, Didin Saefudin, Ganda Putra (Teknik elektro UGM, 2016)
About 10% of collisions resulting in death is due to frontal collision. Head-on Collision Avoidance System (HCAS) is a device that can prevent a frontal collision by means of braking or evasive. Two ultrasonic sensors are used to monitor the vehicles in front and to the right. Two distances are observed by sensors, then become input for decision making system based on fuzzy logic. This decision-making system output is the vehicle forward, stop, or evasive movement. Simulation result using a remote control car proves that the decision making system designed with fuzzy logic can work with a success rate of over 90%.